2019
DOI: 10.1094/pdis-09-18-1698-re
|View full text |Cite
|
Sign up to set email alerts
|

New Oomycota Fungicides With Activity Against Phytophthora cinnamomi and Their Potential Use for Managing Avocado Root Rot in California

Abstract: Phytophthora root rot (PRR), caused by Phytophthora cinnamomi, is the most destructive disease of avocado worldwide. In the United States, mefenoxam and phosphonate products are currently the only registered fungicides for managing avocado PRR. Four new Oomycota-specific and two registered fungicides, all with different modes of action, were evaluated. Seventy-one isolates of P. cinnamomi from avocado in California, most of them collected between 2009 to 2017, were tested for their in vitro sensitivity to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…Similar to observations for other Phytophthora species, oxathiapiprolin was effective against mycelial growth and zoospore germination at concentrations far below 1 μ g/ml (Table 1). Indeed, the measured EC 50 values for mycelial growth indicate that P. agathidicida mycelia are even more sensitive to oxathiapiprolin than well-studied species such as P. capsici and P. cinnamomi (Belisle et al 2019; Ji and Csinos 2015; Miao et al 2016b). Oxathiapiprolin was also effective at delaying or preventing the infection of kauri leaves, albeit at higher concentrations (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similar to observations for other Phytophthora species, oxathiapiprolin was effective against mycelial growth and zoospore germination at concentrations far below 1 μ g/ml (Table 1). Indeed, the measured EC 50 values for mycelial growth indicate that P. agathidicida mycelia are even more sensitive to oxathiapiprolin than well-studied species such as P. capsici and P. cinnamomi (Belisle et al 2019; Ji and Csinos 2015; Miao et al 2016b). Oxathiapiprolin was also effective at delaying or preventing the infection of kauri leaves, albeit at higher concentrations (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Oxathiapiprolin is a novel oomycide that is highly active against many species of Phytophthora at extremely low concentrations (Belisle et al 2019; Gray et al 2018; Ji and Csinos 2015; Pasteris et al 2016). In this study we sought to determine its effectiveness against multiple lifecycle stages of P. agathidicida , the causative agent of kauri dieback disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In California, in vitro sensitivity amongst 71 isolates of Phytophthora cinnamomi collected from avocado orchards demonstrated a broad range of EC 50 values, exhibiting bimodal distribution based on source orchard locations. In southern California where higher rates and more frequent phosphonic acid applications were made isolates were less sensitive than those from northern California where less phosphonic acid was used 74 . Research initiated in the early 1990s to monitor sensitivity of Phytophthora cinnamomi showed that after 10 years of annual trunk injections, there was limited evidence for decreased sensitivity in vitro of isolates from treated compared with untreated trees 75–77…”
Section: The Question Of Resistance or Loss Of Sensitivitymentioning
confidence: 99%
“…Several studies have revealed a very high effectiveness of oxathiapiprolin against various Phytophthora species (Ji et al. 2014;Ji & Csinos 2015;Qu et al 2016;Belisle et al 2019), Pseudoperonospora cubensis (Cohen 2015;Cohen et al 2018) and Plasmopara viticola Leonian 1922 (Pasteris et al 2016). For Plasmopara halstedii (Farl.)…”
mentioning
confidence: 99%